INTEGRATED APPROACH IN NUTRIENT MANAGEMENT OF SESAME WITH SPECIAL REFERENCE TO ITS YIELD, QUALITY AND NUTRIENT UPTAKE - NAYEK, SNEHANGSHU SEKHAR; BRAHMACHARI, KOUSHIK; CHOWDHURY, MD. RITON (The Bioscan, 2014)
An experiment on integrated nutrient management practice for augmenting the productivity of sesame (Sesamum indicum) and improving the soil fertility build-up with different quantum of inorganic nutrients (chemical fertilizers) in conjugation with/without organic manure (FYM and neematex) was carried out in Inseptisol soil of New Alluvial zone of West Bengal, India under subtropical climate at Bidhan Chandra Krishi Viswavidyalaya (State Agricultural University) during the summer and rainy seasons of 2009 and 2010. The experiment was laid out in split plot design replicated thrice with two bio-fertilizer treatments in main plots, six levels of nutrient management practices (combination of organic and inorganic nutrient sources) in sub plots. The relative performances of all the nutrient management practices in terms of plant height, dry matter accumulation, yield attributes, yield and oil content as well as nutrient status of soil (N, P and K status of soil) were assessed. Application of higher doses of inorganic nutrients alongwith neematex increased the yield and oil content. It can be summarized that the application of 40 kg N + 60 kg P2O5 + 40 kg K2O ha-1 in combination with 1t neematex ha-1 exhibited the best results in both summer and rainy seasons in terms of various growth, yield and quality parameters along with soil nutrient status.